Drug Law Enforcement Revisited: The "War" Against the War on Drugs. (July 2017) - Alexandris Polomarkakis, Konstantinos
From the closure of London's nightclub Fabric to Duterte's drug war, law enforcement has become the policy choice par excellence for drug control by stakeholders around the globe, creating a rift between theory and practice, the former vehemently dismissing most of its alleged benefits. This article provides a fresh look on the said regime, through examining its implications in the key areas of illicit drug markets, public health, and broader society. Instead of adopting a critical stance from the start, as much of the literature does, the issue is evaluated from the perspective of a focus on the logic and rationality of drug law enforcement approaches, to showcase from within how problematic the latter are. The article concludes by suggesting at least a reconceptualization of the concept, to give way to more sophisticated policies for finally tackling the issue of illegal drugs effectively.